UAV - Digital Terrain Elevation Model (DTM) from MielleHoga UAV - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2021)
Digital Surface Model generated from photos taken from an UAV platform using photo-stereography techniques. Nominal pixel size is 5 cm.
Abisko Scientific Research Station (2021). UAV - Digital Terrain Elevation Model (DTM) from MielleHoga UAV, 2018-07-28 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/PdyzyQfUXUw1E9gpdHlZJ-XE
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; NDVI; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap